Sosialisasi Strategi Pembelajaran Bahasa Inggris di SMAN 1 Seunagan, Nagan Raya, Aceh - Syafitri, Rina; Syahputri, Veni Nella; Setiyana, Rusma (Universitas Teuku Umar, 2025)
This empowering community program at SMAN 1 Seunagan focuses on effective English learning strategies, boosting student motivation and participation, and evaluating their English proficiency and enthusiasm. To enhance English language learning, teachers at SMAN 1 Seunagan have implemented various engaging and relevant teaching strategies. Research results indicate that effective socialization of English language learning involves a context-based approach, technology utilization, teacher training, and continuous evaluation. Student motivation is triggered by material relevance, interactive learning, and positive recognition. Knowledge and skills evaluation is conducted through various methods to provide constructive feedback to students. Student enthusiasm is reflected in active participation, group collaboration, and technology use in learning. In conclusion, the implementation of effective strategies in learning socialization, student motivation, comprehensive evaluation, and fostering student enthusiasm has helped improve the quality of English language learning at SMAN 1 Seunagan, creating a learning environment that supports student growth in facing global challenges.